Implementation of the Morning Al-Qur'an Program to Improve Students' Al-Qur'an Memorization Abilities at MI Integral Hidayatullah, Jayapura City - Tati Tati; Talabudin Umkabu; Luluk Wahyu Nengsih; Zulihi Zulihi; Ika Putra Viratama; Didik Efendi (Edumaspul: Jurnal Pendidikan, 2025)
This study is motivated by the importance of instilling love for the Qur’an from an early age, particularly through structured memorization habits in elementary school environments. MIS Integral Hidayatullah Kota Jayapura has implemented the Morning Al-Qur’an Program as one of its religious learning strategies to enhance students’ memorization skills. The objectives of this research are to describe the implementation of the Morning Al-Qur’an Program at MIS Integral Hidayatullah Kota Jayapura, to analyze the supporting and inhibiting factors of its implementation, and to examine its contribution to improving students’ Qur’an memorization ability. This study employed a qualitative approach with a case study design. Data were collected through observations, in-depth interviews with the principal, Qur’an teachers, and students, as well as documentation. The data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results indicate that the implementation of the Morning Al-Qur’an Program consists of three stages: planning, implementation, and evaluation. The planning stage set gradual memorization targets according to students’ grade levels; the implementation stage was conducted every morning using the talaqqi, tasmi’, and collective muraja’ah methods; and the evaluation stage was carried out at the end of each semester through memorization tests recorded in progress reports and included in religious report cards. Supporting factors of the program include school policy, teacher commitment, parental support, and student enthusiasm. Inhibiting factors consist of limited facilities, student discipline issues, time constraints, and the lack of consistent muraja’ah at home. The program significantly contributed to improving students’ memorization abilities both in quantity and quality, while also fostering discipline, learning motivation, and religious character.